High-ultrahigh temperature metamorphism in the Larsemann Hills:insights into the tectonothermal evolution of the Prydz Bay region, East Antarctica - Wang, Wei-(Rz); Zhao, Yue; Wei, Chunjing; Daczko, Nathan R.; Liu, Xiaochun; Xiao, Wenjiao; Zhang, Zhiyong (Journal of Petrology, 2022)
As one of the widest terranes exposed in icy Antarctica, the Larsemann Hills in the Prydz Bay belt preserves diverse rock types with a complex metamorphic history and thus is critical to the tectono-metamorphic evolution of East Antarctica. Garnet-sillimanite-spinel-cordierite-bearing and garnet-orthopyroxene-bearing granulites are typical rocks in the region. Phase equilibrium modelling and mineral thermometry based on detailed petrological and mineralogical analyses indicate that the granulites underwent extreme metamorphism with peak conditions to ultrahigh temperatures (UHTs). The high-UHT metamorphism is characterised by extremely high dT/dP values (>1000°C/GPa) along a clockwise path with evident decompression at high temperatures and subsequent near isobaric cooling. Textural relationships, in situ NanoSIMS zircon U-Pb analysis, and LA-ICP-MS zircon and monazite dating and trace element analysis indicate protracted tectono-thermal evolution from the latest Neoproterozoic to early Palaeozoic (c. 570-500 Ma), with a prograde stage likely from c. 570 to c. 550 Ma, a peak stage from c. 550 to c. 540 Ma, and a retrograde stage from c. 540 to c. 500 Ma. During the retrograde stage, major decompression should have occurred before c. 530 Ma, as indicated by the age of zircon included in spinel, and then near isobaric cooling followed and persisted from c. 530 to c. 500 Ma. The geochronological data contribute to the establishment of the thermaloral framework of the late Neoproterozoic to early Palaeozoic Prydz tectonic event. The results also indicate that the assemblage of the investigated granulites basically resulted from the late Neoproterozoic to the early Palaeozoic tectono-thermal event, and the high-UHT conditions revealed by the granulites in the Larsemann Hills imply a much wider distribution of high heat flow and potential UHT metamorphism in the Prydz Bay region. Both the Larsemann Hills and the Rauer Group may have been in a similar and interrelated tectono-thermal setting from the late ...